Luxuries, necessities, and the allocation of time - Lei Fang; Anne Hannusch; Pedro Silos (Federal Reserve Bank of Atlanta, 2021)
Households enjoy utility from activities that require a combination of time and goods. We classify activities into two types: luxuries and necessities. Luxuries (necessities) are activities for which time and expenditure shares rise (decline) with income. We develop and estimate a model with nonhomothetic preferences and find that time and goods are substitutable in producing activities. Activities are also substitutable among themselves. Hence, wage and price changes cause large reallocations of time and expenditures across activities. This effect is quantitatively important for welfare inequality. Since 2003, the rise in the price of leisure luxuries has reduced welfare inequality while the rise in wage dispersion has increased it.
Keywords: J22; E21; D11; 330; time allocation; consumption expenditures; luxuries; necessities; activity production; inequality